2018
DOI: 10.1002/jcsm.12345
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoural adipose tissue pro‐inflammatory cytokines are associated with tumoural growth factors in cancer cachexia patients

Abstract: BackgroundCancer cachexia (CC) is a multifactorial syndrome, often irreversible, that affects patients with cancer influenced, in part, by the inflammatory condition. Peritumoural adipose tissue produces adipokines and angiogenic, apoptotic, and growth factors; given the possible crosstalk between the peritumoural adipose tissue and tumour, these may play an important role in cancer biology and carcinogenesis.MethodsThe aim of this study was to evaluate the factors produced by peritumoural adipose tissue in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
0
22
1
3
Order By: Relevance
“…In the last years, data from clinical studies have implicated pro‐inflammatory cytokines in the pathogenesis of CAC. In previous studies, we demonstrated that the tumour micro‐environment and the adipose tissue contribute to systemic pro‐inflammatory profile and to the alterations of immunomodulatory function in cachectic patients . Zhang et al .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the last years, data from clinical studies have implicated pro‐inflammatory cytokines in the pathogenesis of CAC. In previous studies, we demonstrated that the tumour micro‐environment and the adipose tissue contribute to systemic pro‐inflammatory profile and to the alterations of immunomodulatory function in cachectic patients . Zhang et al .…”
Section: Introductionmentioning
confidence: 81%
“…Recently, we demonstrated higher expression of STAT-1 in the adipose tissue of cachectic patients, which was correlated with increased inflammation, as compared with WSC. 20 STAT-1 has been shown to present an antitumourigenic and anti-proliferative role in both human and murine studies, 65 while other studies show that the increase of STAT-1 is related to oesophageal cancer invasion associated with p53 mutation, tumour growth, and immune evasion. 63,66 Tauriello et al (2018) showed that increased content of TGF-β in the tumour micro-environment could represent a primary mechanism for immune evasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pro-inflammatory factors could mediate tissue damage; in particular, TNF-α can directly recognize death domain to active caspase-8/3 pathways, leading to apoptosis [45,46]. Prolonged exposure to low concentrations of TNF-α can result in cachexia, a wasting syndrome, which can be found in cancer patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, peritumoral adipose tissue has been shown to promote tumor growth and to play a role in inflammation and angiogenesis [88]. A study in colorectal cancer patients found that peritumoral adipose tissue in those diagnosed with cancer cachexia (CC) had increased expression of STAT1 compared with that observed in weight-stable patients [89]. The involvement of STAT1 in cancer is complex however, as it has been reported as a tumor suppressor, but can also promote tumor growth (reviewed in [90]).…”
Section: Stats and Obesity-related Cancersmentioning
confidence: 99%